Non-surgical management methods of noncavitated carious lesions - Tellez, Marisol; Gomez, Juliana; Kaur, Sundeep; Pretty, Iain A.; Ellwood, Roger; Ismail, Amid I. (Community dentistry and oral epidemiology, 2013)
Objective To critically appraise all evidence related to the efficacy of nonsurgical caries preventive methods to arrest or reverse the progression of noncavitated carious lesions (NCCls). Methods A detailed search of Medline (via OVID), Cochrane Collaboration, Scielo, and EMBASE identified 625 publications. After title and review, 103 publications were selected for further review, and 29 were finally included. The final publications evaluated the following therapies: fluorides (F) in varying vehicles (toothpaste, gel, varnish, mouthrinse, and combination), chlorhexidine (CHX) alone or in combination with F, resin infiltration (I), sealants (S), xylitol (X) in varying vehicles (lozenges, gum, or in combination with F and/or xylitol), casein phosphopeptide amorphous calcium phosphate (CPP‐ACP) or in combination with calcium fluoride phosphate. All included studies were randomized clinical trials, were conducted with human subjects and natural NCCls, and reported findings that can yield outcomes measures such as caries incidence/increments, percentage of progression and/or arrest, odds ratio progression test to control, fluorescence loss/mean values, changes in lesion area/volume and lesion depth. Data were extracted from the selected studies and checked for errors. The quality of the studies was evaluated by three different methods (ADA, Cochrane, author's consensus). Results Sample size for these trials ranged between 15 and 3903 subjects, with a duration between 2 weeks and 4.02 years. More than half of the trials assessed had moderate to high risk of bias or may be categorized as ‘poor’. The great majority (65.5%) did not use intention to treat analysis, 21% did not use any blinding techniques, and 41% reported concealment allocation procedures. Slightly more than half of the trials (55%) factored in background exposure to other fluoride sources, and only 41% properly adjusted for potential confounders. Conclusions Fluoride interventions (varnishes, gels, and toothpaste) seem to have the most consistent benefit in decreasing the progression and incidence of NCCls. Studies using xylitol, CHX, and CPP‐ACP vehicles alone or in combination with fluoride therapy are very limited in number and in the majority of the cases did not show a statistically significant reduction. Sealants and resin infiltration studies point to a potential consistent benefit in slowing the progression or reversing NCCls.